2009
DOI: 10.1002/jso.21245
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1α secreted by colon cancer cells enhances angiogenesis: The relationship between IL‐1α release and tumor cells' potential for liver metastasis

Abstract: Based on these findings, we conclude that colon cancer cell-derived IL-1alpha up-regulates angiogenesis by modulating stromal cells within the tumor cells' microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…IL-1a, a key inflammatory cytokine, has been reported to be produced by various cancer cells derived from pancreas, lung, ovary and stomach, and to increase the invasive and metastatic capabilities of tumor cells [23,24]. Our data indicate that IL-1a secreted by SCC cells may enhance the CTSK expression of the surrounding Fbs in a paracrine fashion, which turns out to augment the invasive ability of SCC cells with support from CTSK-bearing Fbs.…”
Section: Discussionmentioning
confidence: 54%
“…IL-1a, a key inflammatory cytokine, has been reported to be produced by various cancer cells derived from pancreas, lung, ovary and stomach, and to increase the invasive and metastatic capabilities of tumor cells [23,24]. Our data indicate that IL-1a secreted by SCC cells may enhance the CTSK expression of the surrounding Fbs in a paracrine fashion, which turns out to augment the invasive ability of SCC cells with support from CTSK-bearing Fbs.…”
Section: Discussionmentioning
confidence: 54%
“…A question that could be raised is why the conditioned media from cancer cell lines in this work did not have any pro-inflammatory cytokines, while other studies have shown that malignant cells do produce such interleukins. The possible answer could be that not all colon cancer cells produce cytokines as has been shown by Matsuo et al [24]. It is conceivable therefore, that aspirin affects colon carcinogenesis via several mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…The process of EMT is induced, promoted and regulated by multiple effectors that also regulate EMT dur-ing embryogenesis, including the cytokines interleukin 8 (IL-8), growth factors [epidermal growth factor (EGF), platelet-derived growth factor (PDGF), TGFβ] and ECM components. Interestingly, it has been shown that CRC cells are able to produce such molecules, including IL-1α, IL-1β and tumour necrosis factor alpha (TNF-α) [60][61][62] . Specifically, TGFβ plays a critical role through autocrine and/or paracrine mechanisms.…”
Section: Transition Of Epithelial Cells In the Large Intestinementioning
confidence: 99%